Manajemen Pendidikan Islam Dalam Al-Qur’an - Dermawan Syahputra (Jurnal Dirosah Islamiyah, 2023)
Educational management has a strategic role in shaping human civilization. Existing human civilization is a human formation that has gone through an educational process. This is where the crucial point of education management. The output of an educational process is largely determined by how the place of education is managed. The existence of various educational management and in a long period of time has now given birth to a separate science, namely the science of educational management. Judging from the type of research, there is also the type of research used in this research, namely bibliography research or library research, which is research that is carried out by collecting information or making objective records that mean the object of research or collecting information that has the character of a bibliography, or analysis carried out to uncover a problem which is basically based on critical and in-depth analysis of relevant literature materials. This research results that management is an important thing for humans and especially the world of education which is not denied in the Qur'an. The Qur'an uses a term, namely Al-tadbir to express the meaning of management. Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, nation and state. Keywords: Management, Education, Al-Qur'an